Implementasi Total Quality Management (TQM) dalam Pengelolaan Zakat di Lazisnu Plumpang Tuban - Rozikin, Muhammad; Rosyidah, Irma (Journal of Industrial and Syariah Economics, 2024)
This research talks about the implementation of total quality management in zakat management at LAZISNU Plumpang. Total quality management is an approach to running a business that tries to maximize organizational competitiveness through continuous improvement of products, services, people, processes and the environment. Therefore, the author formulates the problem 1) what is the process of implementing Total Quality Management in zakat management at LAZISNU Plumpang? 2) What efforts has LAZISNU Plumpang made to improve TQM for zakat management? 3) what are the obstacles of Total Quality Management in managing zakat. This research uses a qualitative descriptive approach by collecting data that is collected laterinterpreted with words. This research uses observation methods, structured interviews and documentation. After obtaining the data, the author can conclude that TQM is a strategy to maximize competitiveness that is oriented towards customer satisfaction with the goods and services offered by the organization. By maximizing employee performance in order to achieve organizational improvement and progress.